Interv'iu ministra vnutrennikh del Rossiiskoi Federatsii . Interv'iu ministra vnutrennikh del Rossiiskoi Federatsii . Interview of the Minister of Internal Affairs of the Russian federation . Интервью министра внутренних дел Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the Minister of the Internal Affairs of Russia, Andrei Kozyrev. Featured in the program: Kozyrev, Andrei Vladimirovich (Minister of Internal Affairs of the Russian Federation) Интервью с министром внутренних дел России Андреем Козыревым. В программе участвуют: Козырев, Андрей Владимирович (Министр внутренних дел Российской Федерации)